2005
DOI: 10.17221/5640-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The effects of humic acid on egg production and egg traits of laying hen

Abstract: ABSTRACT:The effects of humic acid on feed consumption, egg production, feed efficiency, egg weight and external and internal egg quality of laying hens were studied during feeding periods. A total of 180 (Hysex Brown) layers (36 weeks of age) were used in this experiment. There was one control and two experimental groups, each containing 60 hens and 4 subgroups. The experimental period lasted 16 weeks. At the end of the experiment, the supplementation of humic acid had a significant effect on feed consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
20
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 6 publications
(4 reference statements)
8
20
0
8
Order By: Relevance
“…These results are in agreement with the results of studies involving hens on supplementations of humate (Kucukersan et al, 2005;Yoruk et al, 2004) and boric acid (Qin & Klandorf, 1991;Wilson & Ruszler, 1996;Mizrak & Ceylan, 2009). Mizrak & Ceylan (2009) tried to determine different level of B (25, 50, 75 ppm) effects on laying hens.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are in agreement with the results of studies involving hens on supplementations of humate (Kucukersan et al, 2005;Yoruk et al, 2004) and boric acid (Qin & Klandorf, 1991;Wilson & Ruszler, 1996;Mizrak & Ceylan, 2009). Mizrak & Ceylan (2009) tried to determine different level of B (25, 50, 75 ppm) effects on laying hens.…”
Section: Discussionsupporting
confidence: 89%
“…Yoruk et al (2004) reported that supplementation of humate into the diet at level of 0.1 and 0.2% during the late laying period improved feed conversion ratio, increased egg production and reduced mortality. Moreover, Kucukersan et al (2005) reported that addition different amount of humate (30 and 60 ppm) into layer diets showed significant results about egg production, egg weight and feed efficiency (p < 0.05). However, previous studies (Kucukersan et al, 2004;Hayirli et al, 2005) showed that egg production and egg shell quality parameters were not affected by dietary addition of humate in layers.…”
Section: Effects Of Boric Acid and Humate Supplementation On Performamentioning
confidence: 99%
“…The mentioned authors confirmed favourable effect of humic substances at these concentrations in several observed parameters (feed conversion, egg size, shell strength, etc.). Kucukersan et al (2005) observed nonsignificant differences of egg quality between control and experimental groups. They confirmed that the dietary supplementation of humic acids at doses 30 and 60 g t -1 of feed can be used to improve egg production, egg weight and feed efficiency.…”
Section: Resultsmentioning
confidence: 76%
“…The highest quality fractions of humic substances are humic acids which are used in veterinary medicine for the treatment of diarrhea, malnutrition, dyspepsia and acute intoxication (EMEA, 1999). The positive effect of humic substances on the growth of animals, feed conversion (Kocabağli et al, 2002;El-Husseiny et al, 2008;Ozturk et al, 2012;Mirnawati and Marlida, 2013), hatchability of hens (Yörük et al, 2004;Kucukersan et al, 2005) and the viability of animals (Eren et al, 2000;Karaoglu et al, 2004;Esenbuğa et al, 2008) were observed in many studies. Because of their ability to promote the animal growth they could be suitable alternative for antibiotic growth promoters which utilization is prohibited in animal nutrition in the EU since 2006.…”
Section: Introductionmentioning
confidence: 96%
“…Humic-mineral preparation Humokarbowit-Hkw and humine-fat preparation Humobentofet-Hbf are produced in Poland [77,78]. The humine additives generally have a positive influence on the production results, the health status of laying hens and the quality of chicken eggs from intensive [79,80] as well as from ecological and extensive breeding systems [81,82] studied the application of Humokarbowit and Humobentofet enriched with fish oil and linseed oil in feeding Lohmann Brown laying hens. In phase III of the laying period they observed an overall increase of egg-yolk fat and better fatty acid profile in egg-yolk total lipids.…”
Section: Pc Pementioning
confidence: 99%